The sophrology as adjuvant therapy may improve the functionality of patients with fibromyalgia. A pilot randomized controlled trial - Oliveira, Franciele Santos de; Silva, Hugo Jario de Almeida; Oliveira, Jaine Maria de Pontes; Silva, José Felipe Costa da; Gomes, Valéria Lidyanne Silva; Fonseca, Diogo Simões; Lins, Caio Alano de Almeida; Souza, Marcelo Cardoso de (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Sophrology is the science of the serene spirit applied to human consciousness. Body relaxation exercises are not yet a consensus in the treatment of fibromyalgia. Objective: To investigate the effectiveness of a relaxation exercise program based on sophrology in patients with fibromyalgia. Method: This is a pilot study, controlled, randomized and with blinded evaluator and eighteen patients with medical diagnosis of fibromyalgia were randomized into two groups: the intervention group (IG) who participated in sophrology sessions (n= 8) and control group (CG) who participated of a resistance training program (n= 10). Both groups underwent treatments 2 times per week for 12 weeks and reevaluations every 4 weeks. The assessment instruments used were the visual analogic scale of pain (VAS), the satisfaction with the treatment by the Likert scale, the 6-minute walk test (6MWT), the Timed Up and Go test (TUG) and the Fibromyalgia Impact Questionnaire (FIQ). Results: We did not find statistical differences in any of the variables between the groups. The intragroup evaluation, there was a significant difference in CG for TC6 (p= 0.01) and TUG (p= 0.04). In IG there was a statistically significant difference (p = 0.02) for the FIQ. Conclusion: Thus, the improvement in 6MWT and TUG in the CG and the improvement in the FIQ in the IG group showed promising results, although studies with larger sample is needed for more accurate results.